Pengaruh Metode Pembelajaran Two Stay Two Stray Terhadap Kemampuan Berpikir Kritis Matematika - Wulandari, Nadya Khoifah; Suhendri, Huri; Idha isnaningrum (CV Putra Publisher, 2024)
This research endeavor seeks to examine the impact of the Two Stay Two Stray learning approach on critical thinking skills in the field of mathematics. The research adopts an experimental model employing a Post-Test Only Control Group Design research design. The research sample consists of two classes, namely the experimental class utilizing the Two Stay Two Stray learning method, and the control class employing the Think Pair Share learning method, with each class consisting of 20 students from MTs Ashnawiyah and MTs Gunung Putri. Data is collected through an objective essay-based test, which has been validated on 20 students outside the sample, through assessments of validity, reliability, and question difficulty levels. Pre-requisite tests for data analysis include a normality test using the Liliefors Test and a homogeneity test using the Fisher Test, yielding a result of 2.046. Hypothesis testing is conducted via the t-test, resulting in a tcount > ttable, thus leading to the rejection of H0. The research findings indicate a significant influence of the Two Stay Two Stray learning method on critical thinking skills in mathematics. Hence, this instructional approach can be considered as an alternative for educators to foster an active, effective, and engaging learning environment